A COMUNICAÇÃO NO MERCADO DO IMATERIAL: Tensões e distensões da produção simbólica em uma era pós-material - Malta, Renata Barreto (2013)
This thesis is constituted by two complementary stages, the theoretical and the empirical ones, which are essential to reach the following aims we have proposed. 1) Confirming a change in the publicity praxis in which material and functional elements become less relevant and immaterial and intangible elements more important. 2) Investigating, objectively and comparatively, the corpus content, demonstrating which themes prevail in different social periods and punctuating their tangible and intangible essence. 3) Presenting and delineating the Market of Immaterial , the outline of a new model of marketing segmentation which has the immateriality as base. The theoretical discussion based on Cultural Studies and in authors who discourse about the Post Modernity and its consumption relations is the bottom-line of this research and only by it we could elaborate the assumptions which have originated the two hypotheses, extremely connected, which sustain this thesis. The empirical research applies as a method the quantitative content analysis of the corpus, composed by advertising videos, carefully defined. Following the analytical and theoretical path, it was possible to conclude that we are in a post material era, ruled by the intangible, which modifies the market communication.